Federated Deep Reinforcement Learning for Adaptive Spectrum Allocation in Dense 5G-A Wireless Networks - Zaid J. Reed; Kriti Grover (Computational Intelligence Systems, 2026)
The evolution of fifth-generation advanced wireless systems has intensified the complexity of spectrum allocation in dense heterogeneous communication environments characterized by massive device connectivity, ultra-low latency requirements, network slicing, edge intelligence, and highly dynamic traffic behavior. Traditional spectrum management approaches based on static assignment, centralized optimization, or isolated learning architectures have demonstrated limited scalability under rapidly changing radio conditions and geographically distributed service demands. This paper investigates the integration of federated deep reinforcement learning as a distributed intelligence paradigm for adaptive spectrum allocation in dense 5G-A wireless networks. The study explores how federated collaborative learning mechanisms enable decentralized base stations, edge nodes, and network controllers to jointly optimize spectrum utilization while preserving local operational autonomy and minimizing raw data exchange. The paper develops a system-level analytical framework examining the interaction between spectrum scarcity, edge orchestration, interference management, mobility-aware optimization, and trust-aware policy coordination across heterogeneous radio access infrastructures. Particular attention is given to governance challenges associated with fairness, privacy preservation, model drift, communication overhead, and energy sustainability within large-scale wireless ecosystems. The analysis further evaluates the architectural implications of integrating deep reinforcement learning with federated coordination under high-density urban deployments, industrial communication systems, vehicular networking environments, and critical infrastructure services. Beyond performance optimization, the paper emphasizes the broader socio-technical implications of intelligent spectrum orchestration, including regulatory adaptation, infrastructure inequality, environmental efficiency, and operational resilience. The findings indicate that federated deep reinforcement learning provides a viable pathway toward scalable, adaptive, and resilient spectrum governance for next-generation wireless ecosystems, particularly when supported by cross-layer coordination, policy-aware deployment strategies, and robust edge intelligence frameworks.